Multitarget mechanisms of the herb pair Achyranthes bidentata and Paeonia lactiflora Pall. in ameliorating hypertensive cardiomyopathy: combining network pharmacology and functional exploration - Zhang, Yanyan; Wang, Yingwanqi; Liu, Jianing; Zhao, Yu; He, Yuhui; Yan, Peimei; Ren, Shan; Lyu, Ying; Jia, Weiwei; Sun, Yuran; Lin, Song; Lin, Yan (Frontiers in Pharmacology, 2026)
The herb pair Achyranthes bidentata Blume and Paeonia lactiflora Pall. (AB-PL) has demonstrated significant efficacy in the treatment of hypertensive cardiomyopathy; however, its underlying mechanisms remain unclear. In this study, we established an integrated framework combining predictive network pharmacology and experimental exploration to investigate the action mechanisms of AB-PL. The potential antihypertensive targets and pathways of AB-PL were predicted via network pharmacology analysis. These predictions were further explored and assessed in a hypertensive C57 mouse model using real-time quantitative polymerase chain reaction (RT-qPCR), Western blotting, immunohistochemistry, metabolomics, and other assays. The network pharmacology analysis suggested that the active components of AB-PL (e.g., paeoniflorin) may alleviate hypertensive cardiomyopathy by modulating nitrogen metabolism, oxidative stress, inflammation, and the lipid metabolic pathways. Our experimental results show that AB-PL significantly reduces blood pressure and decreases the levels of atrial and brain natriuretic peptides while improving left ventricular ejection fraction in hypertensive mice. AB-PL treatment also ameliorates abnormalities in the nitrogen metabolism biomarkers. Fluorescent probe detection, RT-qPCR, and immunohistochemical analyses indicate that AB-PL significantly alters the expression levels of reactive oxygen species, superoxide dismutase, Keap1, Nrf2, and HO-1. In addition, AB-PL suppresses inflammatory responses by inhibiting the expression of NLRP3, ASC, gasdermin D, IL-1β, and IL-18. Metabolomic analysis further suggested the regulatory effects of AB-PL on the lipid metabolism pathways, including fatty acid biosynthesis. In conclusion, this study provides insights into the potential antihypertensive cardiomyopathic mechanisms of AB-PL through a combined bioinformatic and experimental approach, which support its potential clinical application for the prevention and treatment of hypertensive cardiomyopathy.